Optimizing ZIS for Social Welfare: Integrating Religious Values, State Policy, and the Role of Social Workers in Indonesia - Budi Rahman Hakim; Panji Putrawan Makalalag (Smart Society, 2025)
Despite numerous welfare programs, poverty and inequality persist in Indonesia. Islamic philanthropic instruments such as Zakat, Infaq, and Sadaqah (ZIS) hold great potential to complement state efforts. However, their effectiveness is hindered by fragmented governance, low public trust, and the underutilization of professional social workers. This study aims to conceptualize an integrative model for optimizing ZIS by aligning Islamic values, public policy frameworks, and social work practices. Employing a descriptive qualitative approach through a thematic literature review, this study analyzed academic publications, legal documents, and institutional reports. Findings propose a triadic synergy model comprising Islamic ethical principles, a supportive regulatory environment, and professional social work engagement to enhance inclusive and accountable ZIS governance. The model underscores the importance of distributive justice and sustainable empowerment for marginalized communities. This conceptual framework offers a foundation for developing Islamic social policy and invites empirical validation across diverse regions in Indonesia.